Enhancing Sugar Sales Through Quality Improvement and Customer Preferences: Meningkatkan Penjualan Gula Melalui Peningkatan Kualitas dan Preferensi Pelanggan - Firdaus, Handika; Sukmono, Rita Ambarwati (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates factors influencing the selling price of PT PG Candi Baru's sugar products, utilizing the Importance Performance Analysis (IPA) - Kano method and Quality Function Deployment (QFD). Despite consistent sales growth, the company's selling value needs enhancement. Findings reveal PT PG Candi Baru's superiority in product design, packaging durability, and availability compared to competitors. However, deficiencies in the weight measurement parameter of the 1 kg retail sugar product are noted. Renewing the 1 kilogram retail machine, integrated with a scale with an error rate of less than 0.5, is proposed to address this issue. Additionally, tightening quality control selection related to weight measurement is recommended. This research offers insights for improving PT PG Candi Baru's product competitiveness, contributing to the understanding of customer preferences and suggesting actionable strategies for the company's development. Hightligh: Customer priorities identified: IPA-Kano and QFD methods used. Product superiority: Design, packaging, availability excel. Renewal recommendations: Update machine, improve quality control for weight. Keywords: Sugar products, Selling price, Quality improvement, Industrial engineering, Customer preferences